2001
DOI: 10.1016/s1010-7940(01)00665-0
|View full text |Cite
|
Sign up to set email alerts
|

Should severe monolateral asymptomatic carotid artery stenosis be treated at the time of coronary artery bypass operation?

Abstract: The concomitant treatment (either staged or simultaneous) of SMACS at the time of CABG does not influence the in-hospital results, but confers significant neurological protection during the years after the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…However, by the 34 th month, neurologically based mortality and morbidity increased in patients in the only CABG group ( Figure 3 ), but it remained similar in patients in other groups ( Figure 2 ). The only other study on this particular issue conducted by Gaudino M. et al [ 26 ] reported similar results for their 139 patients. They observed an increase in neurological events in only CABG patients with severe asymptomatic and unilateral carotid stenosis at the mid-term follow-up period.…”
Section: Discussionsupporting
confidence: 62%
“…However, by the 34 th month, neurologically based mortality and morbidity increased in patients in the only CABG group ( Figure 3 ), but it remained similar in patients in other groups ( Figure 2 ). The only other study on this particular issue conducted by Gaudino M. et al [ 26 ] reported similar results for their 139 patients. They observed an increase in neurological events in only CABG patients with severe asymptomatic and unilateral carotid stenosis at the mid-term follow-up period.…”
Section: Discussionsupporting
confidence: 62%
“…In a study of 139 consecutive patients with severe, unilateral, asymptomatic CAS undergoing CABG (73 patients having no carotid artery surgery and 66 patients having CEA), Gaudino et al 21 reported no differences in the inhospital rates of stroke (0% versus 0%; Pϭ1.0) or mortality (1.4% versus 1.5%; PϾ0.05). However, during follow-up (Ͼ5 years), more patients in the no carotid surgery group developed cerebral events ipsilateral to the CAS (24.3% versus 1.6%; PϽ0.0001), whereas 18% required carotid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless D'Agostino et al showed that the risk of perioperative stroke is <2% in patients with carotid stenosis <50%, 10% with stenosis of 50% to 80%, and 11% to 19% with stenosis >80% 13 . A recent study 14 concluded also that the treatment, either staged or simultaneous, of unilateral asymptomatic carotid artery stenosis, at the time of CABG, confers significant neurological protection during the years after surgery. Patients with coronary artery disease and carotid artery stenosis are different from patients with isolated carotid artery stenosis because they are more seriously ill and clinically compromised; therefore, it is not completely right to draw conclusions from the randomized studies about carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%